COVID-19: A global transplant perspective on successfully navigating a pandemic - Kumar, Deepali (Am J Transplant, 2020)
The COVID-19 pandemic has rapidly evolved and changed our way of life in an unprecedented manner. The emergence of COVID-19 has impacted transplantation worldwide. The impact has not been just restricted to issues pertaining to donors or recipients, but also health-care resource utilization as the intensity of cases in certain jurisdictions exceeds available capacity. Here we provide a personal viewpoint representing different jurisdictions from around the world in order to outline the impact of the current COVID-19 pandemic on organ transplantation. Based on our collective experience, we discuss mitigation strategies such as donor screening, resource planning, and a staged approach to transplant volume considerations as local resource issues demand. We also discuss issues related to transplant-related research during the pandemic, the role of transplant infectious diseases, and the influence of transplant societies for education and disseminating current information.